2019
DOI: 10.1021/acs.est.8b06974
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurements of Explosive Compound Dissolution Fluxes from Exposed Munition Material in the Baltic Sea

Abstract: Underwater munitions containing millions of tons of toxic explosives are present worldwide in coastal marine waters as a result of unexploded ordnance and intentional dumping. Dissolution flux of solid explosives following corrosion of metal munition housings controls exposure of biological receptors to toxic munition compounds (MC; including TNT: 2,4,6-Trinitrotoluene, RDX: 1,3,5-Trinitro-1,3,5-triazinane, and DNB: 1,3-Dinitrobenzene). Very little is known about the dissolution behavior of MC in the marine en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…It has been anticipated that very high and toxic concentrations may appear in the sediment and sediment pore water in the close vicinity of a munition fragment, but only a short distance away the concentrations may drop to non-toxic and non-detected levels (Beck et al 2019 ; Rosen and Lotufo 2010 ). This may indeed be true for a complete and/or corroding encased mine as a point source of munitions chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been anticipated that very high and toxic concentrations may appear in the sediment and sediment pore water in the close vicinity of a munition fragment, but only a short distance away the concentrations may drop to non-toxic and non-detected levels (Beck et al 2019 ; Rosen and Lotufo 2010 ). This may indeed be true for a complete and/or corroding encased mine as a point source of munitions chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Water samples collected manually by scientific divers at close intervals very near and vertical to the exposed munitions surface yielded 3100 μg × l −1 dissolved TNT directly at a piece of solid hexanite, whereas concentrations declined rapidly away from the hexanite surface, to 16 μg × l −1 at a 1 cm distance and finally to 3.3 μg × l −1 at a 50 cm distance (Beck et al 2019 ). This explains why the data derived from our studies generally showed elevated levels of explosive chemicals in mussels exposed near the munitions surface, while the concentrations decline upward of the water column.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations